PENGARUH SENAM ASMA TERHADAP FUNGSI PARU (KVP & FEV1) PADA WANITA ASMA DI BALAI KESEHATAN PARU MASYARAKAT (BKPM) SEMARANG - Vironica Dwi Permatasari (Universitas Muhammadiyah Semarang, 2015)
Background: The number of people with asthma in the Community Lung Health Center (BKPM) Semarang there are as many as 851 people in 2010, then in 2011 increased to 1,537 patients. This study aims to determine the effect of gymnastic exercises on pulmonary function (FEV1 & KVP) in women with asthma. Methods: The study was a quasi experiment. The study design was a pretest-posttest reapeted.Population in this study were women with asthma were 35. Samples of this study were women with asthma as much as 33 people. The sampling technique used was purposive sampling. Results: KVP before gymnastics asthma in asthmatic women mostly normal by 48.5%. KVP 4x asthma after exercise in women with asthma are mostly normal by 51.5%. KVP 8x asthma after exercise in women with asthma are mostly normal total of 57.6%. FEV1 before exercise asthma asthma in women mostly normal by 45.5%. FEV1 after exercise in women with asthma asthma 4x mostly normal by 60.6%. FEV1 after exercise in women with asthma asthma 8x mostly normal by 60.6%. There is a difference KVP before and after exercise in women with asthma asthma 4x in Community Lung Health Center (BKPM), Semarang (p value = 0.000). There is a difference KVP beforeand after exercise in women with asthma asthma 8x in Community Lung Health Center (BKPM) Semarang (p value = 0.000). There is a difference in FEV1 before and after exercise in women with asthma asthma 4x in Community Lung Health Center (BKPM), Semarang (p value = 0.000). There is a difference in FEV1 before and after exercise in women with asthma asthma 8x in Hall Lung Health Society (BKPM), Semarang (p value = 0.000). Conclusion: Gymnastics asthma affect the increase in KVP and FEV1